Why didn't you tell me the truth? ＂Report Only Good News＂ - exploring factors of biased reporting in the workplace - Shu-Ching Chang(張淑卿); Yu-Ha Cheung(張雨夏); Hung-Chieh Yen(顏鴻傑); Jen-Wei Cheng(鄭仁偉); Shih-Hao Lu(呂志豪) (Corporate Management Review, 2024)
In many organizations, employees only report good news to their supervisors and fail to highlight potential problems or concerns, in order to maintain harmonious interpersonal relationships and avoid discomfort in communication. We explored this topic using two studies. Study 1 used a qualitative approach to explore constructs of employee silence and voice. Three concepts emerged from our analysis, including the dimensions of selective expression, downplaying, and ostensible expression. These concepts are significant as they form the basis of our scale development in Study 2. Based on these concepts, we developed a nine-item scale, which was validated using exploratory factor analysis and confirmatory factor analysis. The practical and theoretical implications of our results are discussed.